2013
DOI: 10.2478/s13380-013-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the role of tau in Alzheimer’s disease: A unifying hypothesis

Abstract: Recent investigations into the etiology and pathogenesis of Alzheimer's disease (AD) in the past few years have expanded to include previously unexplored and/or disconnected aspects of AD and related conditions at both the cellular and systemic levels of organization. These include how AD-associated abnormalities affect the cell cycle and neuronal differentiation state and how they recruit signal transduction, membrane trafficking and protein transcytosis mechanisms to produce a neurotoxic syndrome capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 261 publications
1
10
0
Order By: Relevance
“…This finding strengthens cytoskeletal abnormalities as a possible pivotal mechanism in neurodegeneration in AD (Terry, 1996; Šimić et al, 1998a), and positioned AD as the most important secondary tauopathy (as the tau-coding MAPT geneitself is not mutated), while mutations in the MAPT gene subsequently identified into a new group of diseases now called primary tauopathies. In the years to follow, both in vitro and in vivo studies have shown that reducing endogeneous tau ameliorates Aβ-induced deficits (Roberson et al, 2007; Bhatia and Hall, 2013; for review see Wang and Mandelkow, 2016), which provided compelling evidence that tau is sufficient and necessary for Aβ-induced neurodegeneration.…”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…This finding strengthens cytoskeletal abnormalities as a possible pivotal mechanism in neurodegeneration in AD (Terry, 1996; Šimić et al, 1998a), and positioned AD as the most important secondary tauopathy (as the tau-coding MAPT geneitself is not mutated), while mutations in the MAPT gene subsequently identified into a new group of diseases now called primary tauopathies. In the years to follow, both in vitro and in vivo studies have shown that reducing endogeneous tau ameliorates Aβ-induced deficits (Roberson et al, 2007; Bhatia and Hall, 2013; for review see Wang and Mandelkow, 2016), which provided compelling evidence that tau is sufficient and necessary for Aβ-induced neurodegeneration.…”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…These include the appearance of cell cycle markers (64) and ectopically sprouting axonlike processes (NTs) emerging from the dendrites (45, 6567) during the development of neurofibrillary lesions in neurodegenerative tauopathies. Dendritic NTs in particular suggest that tau functions in the development of axonal identity may play a role in the early stages of AD where they may reflect damage to mechanisms that maintain the terminally differentiated neuronal state (68, 69). The “fetal” (3R0N) tau isoform is the shortest three repeat tau isoform with the lowest binding affinity for MTs (30), possibly reflecting the far greater importance of tau N-terminal interactions and functions during development relative to the role tau plays in the mature CNS.…”
Section: Overviewmentioning
confidence: 99%
“…Overexpression of tau in culture causes cells to secrete exosomes containing tau that has been phosphorylated at several proline-directed sites (106), possibly as a protective response to high concentrations of membrane-associated tau (206). Overall, it appears that tau may be secreted via multiple mechanisms from neurons in tauopathy, including microvesicle shedding, exosomal secretion via endocytosis and fusion with multivesicular bodies, and exophagy, a pathway involving the diversion of autophagosomes to exosomes (69, 81, 134, 207). Uptake mechanisms into trans-synaptic and adjacent cells have been characterized in even less detail that have tau secretion pathways.…”
Section: Current Foci Of Tauopathy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…From a genetic perspective AD can be classified into two subtypes, familial or sporadic, and while the symptomatology and the progression of both forms are comparable, the etiology is fundamentally different [12]. Familial AD accounts for only 5–10 % of the disease cases and is related to the existence of genetic mutations in specific genes, such as those encoding amyloid precursor protein ( APP ) and presenilin ( PSEN ) 1 ( PSEN1 ) and PSEN2 [1320], which are all involved in the production of Aβ.…”
Section: Introductionmentioning
confidence: 99%